(untitled) (Research, Society and Development, 2020)
The study aimed to evaluate the production of mini plants of Zinnia elegans in substrates with different concentrations of compost based on agroindustry residue. To conduct the experiment, a completely randomized design was used, with nine replications. The treatments consisted of five different concentrations of Ecosolo® substrate (0, 25, 50, 75 and 100%), in which Zinnia elegans was cultivated. The characteristics of plant height, stem diameter, number of leaves, flower diameter and number of petals were evaluated. With the exception of the number of leaves, all variables were increased linearly, as the participation of Ecosolo® in the formation of the substrate was high. In this way, it was concluded that Ecosolo® partially or totally replaces the peat substrate in the production of mini plants of Z. elegans, increasing the biometric characteristics as the product concentrations increase.